1996
DOI: 10.1111/j.1365-2389.1996.tb01374.x
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of aluminium in strongly acidified sandy soil in Poland

Abstract: Organically-bound A1 in acidic, base-poor sandy soils seems to be a major contributor to dissolved Al. This hypothesis has been tested under field conditions at two intensely acidified sites. The research was conducted at the agricultural trial fields at Lyczyn, Poland, which have been fertilized continuously for 30 yr with 130 kg ha-' a-' N (as NH4N03 or urea). The effect of depletion of Al on its solubility was also studied.Field data confirmed that mobilized Al originates largely in the organically bound fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…The lower concentration of Al in the rhizosphere are attributed to the formation of Al organic complexes as the rhizosphere contains a wide range of low-molecular-weight organic acids produced by metabolic activities of plant roots and microorganisms. This is in conformity with the findings of Porebska and Mulder (1996), who tested this hypothesis under field conditions and reported that mobilized Al originates largely from the organically found fraction of soil Al.…”
Section: Solution Monomeric Complexed and Exchangeable Aluminum Insupporting
confidence: 92%
See 1 more Smart Citation
“…The lower concentration of Al in the rhizosphere are attributed to the formation of Al organic complexes as the rhizosphere contains a wide range of low-molecular-weight organic acids produced by metabolic activities of plant roots and microorganisms. This is in conformity with the findings of Porebska and Mulder (1996), who tested this hypothesis under field conditions and reported that mobilized Al originates largely from the organically found fraction of soil Al.…”
Section: Solution Monomeric Complexed and Exchangeable Aluminum Insupporting
confidence: 92%
“…A negative relationship of solution Al concentration with tartaric acid indicates more acid excretion by roots under Al-stress condition in acidic soil. Chemical equilibria model predictions indicated that under acidic conditions, addition of citrate was sufficient to reduce free solution Al by about 85%, while a reduction of 73% was found in case of malate (Porebska and Mulder 1996). Jones and Darrah (1994) reported that 18% of the citrate added to an acidic soil was complexed with Al and the degree of Al-citrate complexation was highly dependent on the pH of the soil solution.…”
Section: Relationship Of Organic Acids and Aluminum Concentrationsmentioning
confidence: 97%
“…[21]) most often [20,[22][23][24][25][26][27][28][29][30][31]. A number of researchers [10,20,[32][33][34][35] also recommend water with the intention to closely simulate Al speciation in real soil solution.…”
Section: Introductionmentioning
confidence: 99%